(untitled) (Bangladesh Journal of Zoology, 2025)
Apis spp. are crucial pollinators that support biodiversity, agriculture, and global food production. Proper identification, understanding genetic diversity, and molecular characteristics of honey bee populations are vital for conservation and sustainable beekeeping practices. This study focuses on the DNA barcoding based on partial mt-COI gene sequences of different Apis species in Bangladesh. Samples were collected from various locations across Bangladesh, followed by DNA extraction, polymerase chain reaction (PCR) amplification, and sequencing. By comparing the unique nucleotide sequences of the COI gene to the reference GenBank database, four honey bee species (Apis dorsata, A. cerana, A. florea, and A. mellifera) were identified. Different castes (queen, worker, and drone) of A. mellifera were also sequenced and identified. Over 82% sequence similarity was observed among different species, with nearly 100% commonality within the A. mellifera castes. The mitochondrial A+T content (74%) exceeded G+C (26%). Genetic distance analysis (Kimura’s 2-parameter) indicated minimal divergence between A. dorsata and A. cerana (0.120). Phylogenetic analysis revealed significant genetic variations among different Apis species. A. florea showed the highest mutation rate (40 steps) from its immediate common ancestor. This study enhances the genotypic and phenotypic identification of honey bee species, including A. mellifera castes, in Bangladesh. Bangladesh J. Zool. 53(2): 137-148, 2025